SEJARAH DAN DINAMIKA PEMIKIRAN DALAM MUHAMMADIYAH - Amina; Risda B. Kulibang; Dahlan Lamabawa; Nur Fajar Lamabawa; Miftahul Khaer; Muhammad Adnan (STKIP Subang, 2025)
Muhammadiyah is an Islamic movement that has consistently promoted the spirit of tajdid through the purification of Islamic teachings and social reform since its establishment. This article aims to analyze the history and dynamics of Muhammadiyah’s thought in responding to social, religious, and national changes in Indonesia. This study employs a qualitative approach using a literature review method by examining scholarly works, official Muhammadiyah documents, and other relevant sources. The findings indicate that Muhammadiyah’s thought has evolved dynamically through phases of purification, modernization, and the development of progressive Islam as its ideological framework. These dynamics demonstrate Muhammadiyah’s consistency in preserving Islamic purity while remaining adaptive to contemporary challenges. The study concludes that intellectual flexibility is a key factor in sustaining Muhammadiyah’s role in Indonesia’s religious and social life.